D. W. Griffith : Interviews - Slide, Anthony (Book collections on Project MUSE., 2012)
D.W. Griffith (1875-1948) is one of the most influential figures in the history of the motion picture. As director of The Birth of a Nation, he is also one of the most controversial. He raised the cinema to a new level of art, entertainment, and innovation, and at the same time he illustrated, for the first time, its potential to influence an audience and propagandize a cause. Collected together here are virtually all of the "interviews" given by D.W. Griffith from the first in 1914 to the last in 1948. Some of the interviews concentrate on specific films, including The Birth of a.